Progress in organ 3D bioprinting - Liu, Fan (Int J Bioprint, 2018)
Three dimensional (3D) printing is a hot topic in today’s scientific, technological and commercial areas. It is recognized as the main field which promotes “the Third Industrial Revolution”. Recently, human organ 3D bioprinting has been put forward into equity market as a concept stock and attracted a lot of attention. A large number of outstanding scientists have flung themselves into this field and made some remarkable headways. Nevertheless, organ 3D bioprinting is a sophisticated manufacture procedure which needs profound scientific/technological backgrounds/knowledges to accomplish. Especially, large organ 3D bioprinting encounters enormous difficulties and challenges. One of them is to build implantable branched vascular networks in a predefined 3D construct. At present, organ 3D bioprinting still in its infancy and a great deal of work needs to be done. Here we briefly overview some of the achievements of 3D bioprinting technologies in large organ, such as the bone, liver, heart, cartilage and skin, manufacturing.